Is diffusion-weighted magnetic resonance imaging (DW-MRI) a requirement for suspected cholesteatoma in patients to undergo primary surgery? - Tan, Mehmet; Ozer, Ebru; Bayindir, Tuba; Turan Cicek, Mehmet; Fatih Erbay, Mehmet (Annals of Medical Research, 2021)
Aim: In this study, the aim was to investigate the correlation of preoperative diffusion-weighted magnetic resonance imaging (DW-MRI) with postoperative pathology findings in patients undergoing tympanomastoidectomy with suspicion of primary cholesteatoma.Materials and Methods: The study consisted of the retrospective evaluation of preoperative MRIs, surgical findings and pathology results of patients who underwent tympanomastoidectomy and had preoperative DW-MRI at the Department of Otorhinolaryngology between the years 2017 and 2019.Results: The study was conducted with 199 patients who underwent tympanomastoidectomy surgery. A retrospective examination of patient files revealed that 80 (40.2%) of the patients underwent echoplanar diffusion-weighted magnetic resonance imaging (DW-MRI) because of suspected cholesteatoma in the preoperative period. Of these 80 patients, cholesteatoma was detected in 22 (27.5%) as a result of pathological analysis and/or surgery, but no diffusion restriction was found in MRI interpretation; in 44 (55%) of them, both cholesteatoma in pathological analysis and/or surgery and diffusion restriction in MRI interpretation were detected. In 10 (12.5%) of these 80 patients, cholesteatoma was not detected either in the MRI interpretation or in the pathological analysis and/or surgery. In the remaining 4 (5%) patients, there was a cholesteatoma suspicion in MRI, but it was not detected as a result of pathological analysis or surgery. In this study, the sensitivity of MRI for the diagnosis of cholesteatoma was 66.6%, and its specificity was 71.4%.Conclusion: MRI provides moderately (66.6%) reliable information in the diagnosis of cholesteatoma patients. However, it is more reliable (71.4%) when it comes to exclusion of the disease. Therefore, it should not be used as the sole determining factor in patients who will undergo primary surgery with suspected cholesteatoma. As much as our study results provide guidance for a more accurate use of imaging methods, series with higher numbers of patients are needed.
Keywords: Chronic otit; cholesteatoma; diffusion-weighted magnetic resonance imaging